Impact of ribavirin dosage in chronic hepatitis C patients treated with simeprevir, pegylated interferon plus ribavirin combination therapy. Issue 10 (29th March 2016) - Tahata, Yuki; Hiramatsu, Naoki; Oze, Tsugiko; Urabe, Ayako; Morishita, Naoki; Yamada, Ryoko; Yakushijin, Takayuki; Hosui, Atsushi; Oshita, Masahide; Kaneko, Akira; Hagiwara, Hideki; Mita, Eiji; et al.
Abstract : The factors associated with sustained virologic response (SVR) in chronic hepatitis C (CH‐C) genotype 1 patients treated with simeprevir (SMV), pegylated interferon (Peg‐IFN) plus ribavirin (RBV) triple therapy have not been fully investigated. Two hundred and twenty‐nine treatment‐naïve CH‐C patients treated with SMV triple therapy were enrolled in this study. The overall SVR rate was 87% in per‐protocol analysis. In multivariate analysis, the interleukin (IL) 28B genotype (rs8099917, TT vs. non‐TT, odds ratio [OR]: 0.044, P = 0.001) and RBV dose (< 10/10–12/ ≥ 12 mg/kg/day, OR: 4.513, P = 0.041) were significant factors associated with SVR. In patients with the IL28B non‐TT genotype, RBV dose affected SVR dose‐dependently in stratified analysis of RBV dose ( P = 0.015); it was 44% (8/18) for patients administered <10 mg/kg/day of RBV, 78% (14/18) for those administered 10– 12 mg/kg/day of RBV, and 100% (3/3) for those administered ≥12 mg/kg/day of RBV, whereas in patients with the IL28B TT genotype, a significant correlation between SVR and RBV dose was not observed ( P = 0.229). Regarding RBV dose reduction of less than 10 mg/kg/day, the inosine triphosphate pyrophosphatase (ITPA) genotype (rs1127354, CC vs. non‐CC, OR: 0.239, P = 0.003) and age (by 1 y.o., OR: 1.084, P = 0.002) were significant independent factors. RBV dosage affected SVR dose‐dependently in patients with the IL28B non‐TT genotype treated with SMV triple therapy. Special attention to anemia progression and RBV dosage should be paid to aged patients with the ITPA CC genotype. J. Med. Virol. 88:1776–1784, 2016 . © 2016 Wiley Periodicals, Inc.